Design of hard surfaces with metal (Hf/V) nitride multinanolayers - Escobar, C.; Caicedo, J.C.; Caicedo, H.H.; Mozafari, M. (Сверхтвердые материалы, 2014)
Physical properties as mechanical and tribological evolution on 4140 steel surfaces coated with hafnium nitride/vanadium nitride [HfN/VN]n multinanolayered systems deposited in various bilayer periods via magnetron sputtering has been exhaustively studied in this work. The coatings have been characterized in terms of structural, chemical, morphological, mechanical, and tribological properties by X-ray diffraction, X-ray photoelectron spectroscopy, atomic force microscopy, scanning and transmission electron microscopies, nanoindentation, pin-on-disc and scratch tests. Moreover, the failure mode mechanisms were observed via scanning electron microscopy. The preferential growth in the face-centered cubic (111) crystal structure for [HfN/VN]n multilayered coatings have been shown by X-ray diffraction results. The best enhancement of the mechanical behavior has been obtained when the bilayer period was 15 nm (n = 80), yielding the highest hardness (37 GPa) and elastic modulus was (351 GPa). The values of the hardness and elastic modulus were 1.48 and 1.32 times higher than the coating with n = 1, respectively, as well as the lowest friction coefficient (~ 0.15) and the highest critical load (72 N). These results indicated significant enhancements in mechanical, tribological, and adhesion properties, compared to HfN/VN multilayered systems with bilayer period of 1200 nm (n = 1). The hardness and toughness enhancement in the multilayered coatings could be attributed to the different mechanisms that produce the layer formation with nanometric thickness due to the number of interfaces acting as obstacles for crack deflection and dissipation of crack energy. Due to the emergent characteristics of the synthesized multinanolayered material, the developed adaptive coating could be considered as higher ordered tool machining systems, capable of sustaining extreme operating conditions for industrial applications. Фізичні властивості як механічні і трибологічні зміни на поверхні сталі марки 4140 з покриттям із нанобагатошарових систем нітриду гафнію/нітриду ванадію [HfN/VN]n, нанесених магнетронним розпиленням з різними проміжками між двома шарами, були ретельно вивчені в цій роботі. Структурні, хімічні, морфологічні і трибологічні властивості покриттів визначали дифракцією рентгенівських променів, фотоелектронною рентгенівською спектроскопією, атомно-силовою мікроскопією, растровою та просвічувальною електронною мікроскопією, наноіндентуванням, методом “штифт на крузі” і випробуванням дряпанням. Крім того, механізми відмов спостерігали за допомогою растрової електронної мікроскопії. Результати дифракції рентгенівських променів показали краще зростання (111) граніцентрованої кристалічної структури для багатошарових покриттів [HfN/VN]n. Максимальне підвищення механічних характеристик було досягнуто при товщині бішару HfN/VN, що дорівнював 15 нм (число шарів 80), твердість складала 37 ГПа, а модуль пружності – 351 ГПа. Ці значення твердості і модуля пружності були вище, ніж у покриття з n = 1 (в 1,48 і 1,32 рази відповідно), також це багатошарове покриття мало найнижчий (~ 0,15) коефіцієнт тертя і найвище (72 Н) критичне навантаження. Ці результати показали значне поліпшення механічних, трибологічних і адгезійних властивостей порівняно з HfN/VN багатошарової системою з товщиною бішару 1200 нм (n = 1). Підвищення твердості і в’язкості руйнування багатошарових покриттів може бути пояснено різними механізмами утворювання шарів нанометричної товщини, зумовлених кількістю меж розділу, що діють як перешкоди для відхилення тріщини і розсіювання її енергії. Завдяки покращеним характеристикам синтезованого багатошарового матеріалу, розроблене адаптивне покриття можна розглядати як більш високо впорядковану інструментальну систему обробки, здатну підтримувати екстремальні робочі умови при використанні в промисловості. Физические свойства как механические и трибологические изменения на поверхности стали марки 4140 с покрытием из наномногослойных систем нитрида гафния/нитрида ванадия [HfN/VN]n, нанесенных магнетронным распылением с различными промежутками между двумя слоями, были тщательно изучены в этой работе. Структурные, химические, морфологические и трибологические свойства покрытий определяли дифракцией рентгеновских лучей, фотоэлектронной рентгеновской спектроскопией, атомно-силовой микроскопией, растровой и просвечивающей электронной микроскопией, наноиндентированием, методом “штифт на круге” и испытания царапаньем. Кроме того, механизмы отказов наблюдали посредством растровой электронной микроскопии. Результаты дифракции рентгеновских лучей показали предпочтительный рост (111) гранецентрированной кристаллической структуры для многослойных покрытий [HfN/VN]n. Максимальное повышение механических характеристик было достигнуто при толщине бислоя HfN/VN равной 15 нм (число слоев 80), твердость была равна 37 ГПа, а модуль упругости – 351 ГПа. Эти значения твердости и модуля упругости были выше, чем у покрытия с n = 1 (в 1,48 и 1,32 раза соответственно), также у этого многослойного покрытия был самый низкий (~ 0,15) коэффициент трения и самая высокая (72 Н) критическая нагрузка. Эти результаты показали значительное улучшение механических, трибологических и адгезионных свойств по сравнению с HfN/VN многослойной системой с толщиной бислоя 1200 нм (n = 1). Повышение твердости и вязкости разрушения многослойных покрытий может быть объяснено различными механизмами образования слоев нанометрической толщины, обусловленных количеством границ раздела, действующих как препятствия для отклонения трещины и рассеяния ее энергии. Благодаря улучшенным характеристикам синтезированного многонанослойного материала, разработанное адаптивное покрытие можно рассматривать как более высоко упорядоченную инструментальную обрабатывающую систему, способную поддерживать экстремальные рабочие условия при использовании в промышленности.